“BOOTS AND LIPSTICK: WOMEN WHO MAKE AGRICULTURE GO”: THE PROTAGONISM OF RURAL WOMEN IN CONTEXTS OF INEQUALITY AND INNOVATION IN THE COUNTRYSIDE - da Silva Aroeira, Tarciana Oliveira (Seven Editora, 2025)
This article investigates the strategies of resistance and identity repositioning adopted by women to ensure their permanence and leadership in the rural sector, a space historically marked by patriarchal structures and gender inequalities. Using a qualitative approach and in-depth interviews, the study identifies how these women face symbolic and structural barriers—such as technical discredit, the delegitimization of authority, and harassment—and construct their own forms of leadership. Data analysis reveals a sophisticated repertoire of everyday practices, including assertive positioning, identity camouflage, the reconfiguration of the female image, leadership in management, and the formation of support networks. These strategies engage with the theoretical contributions of Joan Acker, Judith Butler, Erving Goffman, and Gianpiero Petriglieri, demonstrating that female resistance is not limited to protest, but manifests itself as performative, relational, and transformative action. The study contributes to understanding the social mechanisms that sustain the "glass ceiling" in rural areas and points to ways to promote gender equity in agribusiness. It concludes that these female leaders, by transforming their identities and management practices, also reconfigure power dynamics in rural areas, promoting innovation, inclusion, and symbolic recognition.DOI: https://doi.org/10.56238/sevened2025.029-073